Cell cycle arrest of cardiomyocytes in the context of cardiac regeneration - Qingling Xu; Qingling Xu; Xinhui Chen; Chunyige Zhao; Ying Liu; Jianxun Wang; Xiang Ao; Xiang Ao; Wei Ding (Frontiers in Cardiovascular Medicine)
The limited capacity of adult mammalian cardiomyocytes to undergo cell division and proliferation is one of the key factors contributing to heart failure. In newborn mice, cardiac proliferation occurs during a brief window, but this proliferative capacity diminishes by 7 days after birth. Current studies on cardiac regeneration focused on elucidating changes in regulatory factors within the heart before and after this proliferative window, aiming to determine whether potential association between these factors and cell cycle arrest in cardiomyocytes. Facilitating the re-entry of cardiomyocytes into the cell cycle or reversing their exit from it represents a critical strategy for cardiac regeneration. This paper provides an overview of the role of cell cycle arrest in cardiac regeneration, briefly describes cardiomyocyte proliferation and cardiac regeneration, and systematically summarizes the regulation of the cell cycle arrest in cardiomyocytes, and the potential metabolic mechanisms underlying cardiomyocyte cycle arrest. Additionally, we highlight the development of cardiovascular disease drugs targeting cardiomyocyte cell cycle regulation and their status in clinical treatment. Our goal is to outline strategies for promoting cardiac regeneration and repair following cardiac injury, while also pointing toward future research directions that may offer new technologies and prospects for treating cardiovascular diseases, such as myocardial infarction, arrhythmia and heart failure.